A cocoon silk chemistry strategy to ultrathin N-doped carbon nanosheet with metal single-site catalysts - Zhu, Youqi (Nat Commun, 2018)
Development of single-site catalysts supported by ultrathin two-dimensional (2D) porous matrix with ultrahigh surface area is highly desired but also challenging. Here we report a cocoon silk chemistry strategy to synthesize isolated metal single-site catalysts embedded in ultrathin 2D porous N-doped carbon nanosheets (M-ISA/CNS, M = Fe, Co, Ni). X-ray absorption fine structure analysis and spherical aberration correction electron microscopy demonstrate an atomic dispersion of metal atoms on N-doped carbon matrix. In particular, the Co-ISA/CNS exhibit ultrahigh specific surface area (2105 m(2) g(−1)) and high activity for C–H bond activation in the direct catalytic oxidation of benzene to phenol with hydrogen peroxide at room temperature, while the Co species in the form of phthalocyanine and metal nanoparticle show a negligible activity. Density functional theory calculations discover that the generated O = Co = O center intermediates on the single Co sites are responsible for the high activity of benzene oxidation to phenol.